Pemberdayaan Baitul Maal wat Tamwil (BMT) melalui Interbank network sebagai solusi optimasi perekonomian nasional - Nur Ghaziyatul Iffah; Dian Fatma Hadi (Journal of Business & Banking, 2017)
This research aims to see the existence and development of BMT in Indonesia, BMT’s potencial in existing interbank network and to see the steps to optimize the BMT. The method used is descriptive qualitative with secondary data approaches by collecting relevant information based on the topic or problems that are being studied through media such as news, internet sites, journals that discuss about the problem’s issues related with BMT’s role dan giving synthesis based on those information. BMT’s development through the inceasing expansion of network between BMT and Syariah Micro-Financial Entity which is a solution to create a powerful BMT, independent and professional. With the existance of interbank network that based on syariah, hopefully this can be the solution to empower Syariah Micro-Financial Entity to increase sustainably the services quality as form of trust, effort and government’s concern towards Syariah Micro-Financial Entity in the development of national economy.